Inferência em modelos de mistura via algoritmo EM estocástico modificado - Assis, Raul Caram de (Universidade Federal de São Carlos, 2017)
We present the topics and theory of Mixture Models in a context of maximum likelihood and Bayesian inferece. We approach clustering methods in both contexts, with emphasis on the stochastic EM algorithm and the Dirichlet Process Mixture Model. We propose a new method, a modified stochastic EM algorithm, which can be used to estimate the parameters of a mixture model and the number of components.
Inference on mixture models via modified stochastic EM algorithm
Keywords: Modelos de mistura; Mistura de distribuições; Algoritmo EM; Cadeia de Markov; Segmentação de imagens; Mixture models; Mixture of distributions; EM algorithm; Markov chain; Gibbs sampling; Image segmentation; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA